ANALISIS KONSEP DASAR EVALUASI SERTA IMPLEMENTASINYA DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Titin Sunaryati; Nurmalia; Firda Meliawati Putri; Annisa Syifa Fauziah; Eris Fadila Rachmadini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in Indonesia is increasingly developing in accordance with the times, but the development of science and technology in the world of education not only has a positive impact on students but also has a negative impact with the low character of students in the school environment and community environment. The purpose of this study is to determine the effect of educational evaluation on student character education. The approach taken in this study is to use literature studies using scientific sources as a reference in compiling research both obtained from journals, books and related articles that have been validated in previous research. The benefits of this study are 1) knowing the effect of educational evaluation on character education 2) knowing the application of educational evaluation on character education 3) knowing the improvement of student character with the implementation of educational evaluation.